The Plot Thickens: - Anscombe, Jessica (Qualitative and Quantitative Methods in Libraries; 2020: Special issue : COVID-19 and the Libraries : the impact of, 2021)
This paper examines the issues surrounding the closure of a specialist library during the Covid-19 pandemic. The methodology used to gather data was a qualitative survey of 5 library staff members. The results of the survey highlighted the personal and professional challenges each staff member faced and the ways those challenges were overcome to maintain a high standard of library service. The move toward online services and digital lending material is picking up speed and the library can now offer a vast range of material and services remotely. Looking to the future, the face-to-face nature of the screen and broadcast library service may be challenged while how to manage lending services for the physical collection and maintaining the unique visual experience for users will be barriers to overcome.